Development of a Mobility Diet Score (MDS) and Associations With Bone Mineral Density and Muscle Function in Older Adults - Schacht, Simon Rønnow; Lind, Mads Vendelbo; Mertz, Kenneth Hudlebusch; Bülow, Jacob; Bechshøft, Rasmus; Højfeldt, Grith; Schucany, Aide; Hjulmand, Morten; Sidoli, Chiara; Andersen, Søren Binder; Jensen, Mikkel; Reitelseder, Søren; et al. (Frontiers in Nutrition, 2019)
Introduction Risk of both osteoporosis and sarcopenia are major concerns of many older individuals. Reduced bone mineral density (BMD) and muscle function is associated with increased risk of multiple health related issues. Diet may play a role in sustaining BMD and muscle function throughout old age, but much is still to be learned with regards to which specific food groups and dietary patterns that are most important for such outcomes. The aim of the current study was to identify food groups important for both BMD and muscle function. Methods A narrative review was performed on studies published on dietary patterns and their association with BMD and muscle function, respectively. Based on these findings, two dietary indices were constructed characterizing food groups associated with BMD and food groups associated with muscle function, respectively. Associations between adherence to these indices and BMD measured by and muscle function were then investigated in a population of older community-dwelling Danes. Food groups found to be associated with both BMD and muscle function in our study population were suggested for inclusion into a common dietary index named the Mobility Diet Score. Results In contrast to previous studies, adherence to a dietary index based on foods previously linked to BMD could not be established as important for BMD in our study population of 184 older individuals (53.3% men). We found that adhering to a dietary index characterized by higher intakes of whole grains, dairy products, fish, legumes, nuts, fruit and vegetables is associated with faster 400 m walking speeds and an increased number of chair stands measured over a 30 s time period. Since no food group could be established as important for both BMD and muscle function, a Mobility Diet Score could not be established. Conclusion Adherence to a dietary index characterized by high intakes of whole grains, dairy products, fish, legumes, nuts, fruit and vegetables was not found to be associated with BMD in a group of community-dwelling +65 years old Danes . However, our results indicate that the adherence to such foods could be important in sustaining functional capabilities in older individuals.